2013
DOI: 10.7600/jpfsm.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of muscle lengthening: Task- and muscle-specificity

Abstract: We accomplish activities of daily living through a combination of or isolated isometric, shortening (concentric), lengthening (eccentric) contractions regarded as fundamental patterns of muscle activation. It has been widely recognized that a unique neural strategy may control lengthening contractions but it is still unclear if this neural strategy is uniform across muscles. Here we review evidence for task-specific differences in neural control of muscle lengthening and shortening as indexed by surface electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Both groups were recreationally active, but it is possible that the two‐fold increase in male MVC compared to female MVC could be a factor of different training histories. However, it should be noted that neural activation of muscle is task‐specific (Sekiguchi, Nakazawa, Nakazawa, & Hortobágyi, 2013; Uematsu, Sekiguchi, Sekiguchi, Kobayashi, Hortobágyi, & Suzuki, 2011), and the greatest improvements in performance can occur when task‐specific training has taken place (Hirayama, Yanai, Yanai, Kanehisa, Fukunaga, & Kawakami, 2012). Informal questioning indicated that no participant in our study had a training history involving isometric contractions, which suggests that a history of performing isometric elbow flexions did not play a role in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups were recreationally active, but it is possible that the two‐fold increase in male MVC compared to female MVC could be a factor of different training histories. However, it should be noted that neural activation of muscle is task‐specific (Sekiguchi, Nakazawa, Nakazawa, & Hortobágyi, 2013; Uematsu, Sekiguchi, Sekiguchi, Kobayashi, Hortobágyi, & Suzuki, 2011), and the greatest improvements in performance can occur when task‐specific training has taken place (Hirayama, Yanai, Yanai, Kanehisa, Fukunaga, & Kawakami, 2012). Informal questioning indicated that no participant in our study had a training history involving isometric contractions, which suggests that a history of performing isometric elbow flexions did not play a role in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the fibronectin data however revealed that the exercise preferentially damaged FT fibers in muscles that are comprised predominantly ST fibers. Although initial studies suggested a deviation from the orderly recruitment of motor units during eccentric compared with concentric contractions in hand and foot muscles (29,41,42), recent reviews concluded that large vs. small motor units do discharge action potentials at a slower rate during eccentric contractions but the recruitment occurs according the size principle (11,46). In view of new evidence, although the outdated view is still embraced (e.g., study by Cermak et al (4)), it is unlikely that an altered motor unit recruitment is involved in the eccentric exercise-evoked effects on muscle.…”
Section: Discussionmentioning
confidence: 99%
“…E ccentric compared with concentric exercise is associated with unique neural (11,23,25,26,46), biophysical (19,45), metabolic (12), cardiovascular (23,30), and clinical (10,13,33) characteristics and adaptations. Less understood is the muscle fiber-typespecific adaptations following bouts of eccentric exercise.…”
Section: Introductionmentioning
confidence: 99%